Dual‐energy CT quantitative imaging: a comparison study between twin‐beam and dual‐source CT scanners. Issue 1 (10th January 2017) - Almeida, Isabel P.; Schyns, Lotte E. J. R.; Öllers, Michel C.; van Elmpt, Wouter; Parodi, Katia; Landry, Guillaume; Verhaegen, Frank
Abstract : Purpose: To assess image quality and to quantify the accuracy of relative electron densities ( ρ e ) and effective atomic numbers ( Z eff ) for three dual‐energy computed tomography (DECT) scanners: a novel single‐source split‐filter (i.e., twin‐beam) and two dual‐source scanners. Methods: Measurements were made with a second generation dual‐source scanner at 80/140Sn kVp, a third‐generation twin‐beam single‐source scanner at 120 kVp with gold (Au) and tin (Sn) filters, and a third‐generation dual‐source scanner at 90/150Sn kVp. Three phantoms with tissue inserts were scanned and used for calibration and validation of parameterized methods to extract ρ e and Z eff, whereas iodine and calcium inserts were used to quantify Contrast‐to‐Noise‐Ratio (CNR). Spatial resolution in tomographic images was also tested. Results: The third‐generation scanners have an image resolution of 6.2, 0.5 lp/cm higher than the second generation scanner. The twin‐beam scanner has low imaging contrast for iodine materials due to its limited spectral separation. The parameterization methods resulted in calibrations with low fit residuals for the dual‐source scanners, yielding values of ρ e and Z eff close to the reference values (errors within 1.2% for ρ e and 6.2% for Z eff for a dose of 20 mGy, excluding lung substitute tissues). The twin‐beam scanner presented overall higher errors (within 3.2% for ρ e and 28% for Z eff, also excluding lung inserts) and also larger variations for uniform inserts. Conclusions: Spatial resolution is similar for the three scanners. The twin‐beam is able to derive ρ e and Z eff, but with inferior accuracy compared to both dual‐source scanners.